2013
DOI: 10.1007/s10508-013-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Genital Self-image in Pre-menopausal Women with Dyspareunia

Abstract: With a prevalence of 15-21%, dyspareunia is one of the most commonly reported sexual dysfunctions in pre-menopausal women under the age of 40. Studies to date have focused primarily on clinical samples, showing that women with dyspareunia report overall sexual impairment, anxiety, and feelings of sexual inadequacy. However, little is known about their body image and genital self-image and few studies have sampled women exclusively from the general population. The aim of the present, controlled study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 58 publications
2
31
0
3
Order By: Relevance
“…Specifically, a study conducted among a community sample of 330 women showed that, in comparison to pain-free controls, women with vulvovaginal pain reported significantly more distress about their body image and a more negative genital self-image. Moreover, a more negative genital self-image was strongly and independently associated with an increased likelihood of reporting vulvovaginal pain, above and beyond anxiety [20]. In the same community sample of women with vulvovaginal pain, worse self-image cognitions about vaginal penetration contributed uniquely to increased pain intensity, whereas worse self-image cognitions about vaginal penetration and genital self-image contributed to poorer sexual functioning.…”
Section: A Psychological Sexual and Relationship Consequencesmentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, a study conducted among a community sample of 330 women showed that, in comparison to pain-free controls, women with vulvovaginal pain reported significantly more distress about their body image and a more negative genital self-image. Moreover, a more negative genital self-image was strongly and independently associated with an increased likelihood of reporting vulvovaginal pain, above and beyond anxiety [20]. In the same community sample of women with vulvovaginal pain, worse self-image cognitions about vaginal penetration contributed uniquely to increased pain intensity, whereas worse self-image cognitions about vaginal penetration and genital self-image contributed to poorer sexual functioning.…”
Section: A Psychological Sexual and Relationship Consequencesmentioning
confidence: 86%
“…A case in point is vulvodynia: a population-based study suggests that the lifetime cumulative incidence of vulvodynia is 16% [2,3] and its incidence is thought to be increasing in young women [4,5]. In fact, many women suffering from vulvovaginal pain are under the age of 30, with community estimates showing that one in five women aged [18][19][20][21][22][23][24][25][26][27][28][29] report chronic dyspareunia [6]. In addition to disrupting all aspects of sexual function, controlled studies have shown that vulvovaginal pain can adversely affect women and their partners' general psychological well-being, relationship adjustment and overall quality of life [7,8].…”
mentioning
confidence: 99%
“…Furthermore, quality of life is lower in menopausal women due to the high prevalence of sexual dysfunction (2). In a previous study, the frequency of sexual dysfunction was 38.5% and 72.4% among premenopausal and postmenopausal women, respectively (8). Also, the prevalence of sexual dysfunction among Iranian women has been estimated at 31.5% (9).…”
Section: Introductionmentioning
confidence: 90%
“…Women's sexual satisfaction was found to decrease with increasing anxiety levels (Spielberger 1983;Pazmany et al 2013). According to Api (2005), a significant decrease occurs in the sexual activity and libido of women after the menopause, and they also feel anxious due to the reluctance that they experience.…”
Section: The Relationship Between Anxiety Level and Sexual Satisfactionmentioning
confidence: 99%